Preliminary Study on the Lang Neo Mineral Deposits in the Northwest Anticline Structure, Thanh Hoa Province - Quang, Truong Xuan; Xuan Dac, Ngo; Xuan Luan, Truong; Kim Long, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 3, 2025)
Previous studies have indicated that the northwestern region of Thanh Hoa Province has potential mineral resources, particularly deeply buried gold deposits. However, there remain ore occurrences that have not been documented; no prioritization framework has been proposed to evaluate the identified occurrences, and there has not yet been any mineral deposit studied in sufficient detail to carry out sampling work appropriately. The paper addresses the complexity of ore parameters, conditions, environment, and the origin of ore formation, as well as the depth of the ore accumulations, and examines the applicable drill core sample spacing in the Lang Neo mineral deposits. The elements of ore minerals exhibit complex variations, not following the standard distribution, with concentrations ranging from negligible to extremely high. Gold (Au) is paragenetic with the elements Cu, Zn, Sb, and Ag. The low-resistivity zone coincides with the fractured rock zone, where sulphidized porphyroid-textured metamorphic rock lenses are present, associated with gold-bearing hydrothermal sulphide veins and vein systems. The gold ore zone is extensive, located at depths of approximately 250–600 m, and has a steep inclination. In some locations, the gold ore bodies occur in pocket or lenticular forms. These preliminary results could provide a scientific basis for gold resource evaluation in the studied deposit and other areas in the future.